Penerapan Metode WASPAS Dalam Pemilihan Perguruan Tinggi Bagi Siswa Sekolah - Juanda Hakim Lubis; Debi Gusmaliza; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
There are so many high school students who do not understand their own criteria because they are confused about choosing the best college. So that most students choose colleges according to the interests of their friends, without finding out which colleges match their criteria. Not even a few of these students follow the directives of their parents. As a result of this, it causes major errors, regrets studying at these institutions and some even move and some even stop. Though each major is tailored to the wishes of students in the future. So that these problems can be solved, then a decision support system is made which will make it easier for students who want to continue to a bachelor's degree or diploma. There are many methods used in decision support systems, one of which is used in this study is the WASPAS method. The way WASPAS works is easy to reach, resulting in a sequence of universities and majors according to their respective criteria, starting from the highest to the lowest. After being applied with the WASPAS method, the final result is the best alternative in alternative A2 with a result value of 14,297.